Relationship of swimming power to sprint freestyle performance in females - Boelk, A. G.; Norton, J. P.; Freeman, J. K.; Walker, A. J. (Medicine & Science in Sports & Exercise, 1997)
Female collegiate (N = 20) and club (N = 14) swimmers were measured for swimming power and sprinting velocity. Power was measured using a seven-trial increasing-resistance protocol on a Power Rack. Sprint velocity was determined for a 25-yd swim. Each of the seven power tests were moderately correlated (range .58 to .84) with sprinting velocity. Peak power and mean power were also correlated significantly with sprinting velocity. When factors were combined into regression equations, 73% of sprinting velocity was associated with Power Rack variables. The relationship was higher in club swimmers (85%) than college swimmers (76%). Implication. Power Rack measures are associated with swimming velocity more in female club than college swimmers. The level of relationships suggests that Power Rack measures are not sensitive enough to evaluate training effects in well-trained groups of female swimmers. This is because in females, anaerobic and power improvements are quite restricted and much less than the level of "unrelatedness" reported in this study. The best measure of swimming power in females remains swimming time for 25 yards.